Answer:
C
Explanation:
We want to solve the equation:
![x^2+2x+7=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/i70yvgllxvs6x9xkmqogbk25582s8jdzo4.png)
Using the quadratic formula. The quadratic formula is given by:
![\displaystyle x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2022/formulas/mathematics/high-school/iipuedmc7a1mozjrvbx5z80tpb75pjqmzg.png)
In this case, a = 1, b = 2, and c = 7.
Substitute:
![\displaystyle x=(-(2)\pm√((2)^2-4(1)(7)))/(2(1))](https://img.qammunity.org/2022/formulas/mathematics/high-school/oc176bolno1ru4chm4iexsm5b1fl9yo6cu.png)
Evaluate:
![\displaystyle x=(-2\pm√(-24))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/tfrzv9tz0ocbeacaj45hs1ym6bhuqq3w5i.png)
Simplify the square root:
![√(-24)=√(4\cdot 6\cdot -1)=√(4)\cdot√(6)\cdot√(-1)=2i√(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/pfmojhp6t5j7ula7i0vu8h5e6ck9ufhaqb.png)
Hence:
![\displaystyle x=(-2\pm2i√(6))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/qpciizzx4pzadumkm775ctfc7nxk7uldf5.png)
Simplify:
![\displaystyle x=-1\pm i√(6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/i91t4o0rxw6iz15isv202dhevt2g5i8o2q.png)
Hence, our solutions are:
![\displaystyle x=\left\{-1+i√(6), -1-i√(6)\right\}](https://img.qammunity.org/2022/formulas/mathematics/high-school/pvtx7t4eju78xcpyg40ibcf1nm5k21pt96.png)
Our answer is C.